Pemanfaatan tepung daun kelor (Moringa oleifera Lamk) dengan pretreatment asam dan tepung ikan lele terhadap pemulihan anemia secara in vivo - Ayutha Wijiindyah; Syaiful Anwar; Sri Hetty Susetyorini (Jurnal Gizi Klinik Indonesia, 2012)
Background: It is estimated more than 50% of the cases of anemia in the world is caused by iron (Fe) deficiency, it needs alternative sources local food that rarely used but cheap.Objective: This monofactorial experiment was done to find out whether kelor leaves powder resulted from acid pretreatment and addition of catfish powder can support the recovery of iron deficiency anemia, based on an in vivo study with iron (Fe) and hemoglobin (Hb) measurements.Methods: The experiment was a trial of anemia recovery by providing 42 wistar rats with no iron-containing feeding for 7 days, then continued for 14 days with either one of six kinds of feeding: standard feeding of AIN-93 M, kelor leaves powder or catfish powder (as control), kelor leaves powder with 0.5% citric acid pretreatment, kelor leaves powder with 0.5% citric acid pretreatment and catfish powder (1:1), kelor leaves powder with 0.5% lime pretreatment, or kelor leaves powder with 0.5% lime pretreatment and catfish powder (1:1). Criteria of anemia recovery was Fe value > 80 µg/dl and Hb > 10 g/dl. Statistical analysis was performed by using ANCOVA and LSD test.Results: The in vivo study showed that feeding rats with kelor leaves powder (respective Fe and Hb value was 101.22 µg/dl and 11.17 µg/dl), with 0.5% citric acid pretreatment (respective Fe and Hb value was 90.36 µg/dl and 10.68 µg/dl), with 0.5% lime pretreatment (respective Fe and Hb value was 115.51 µg/dl and 12.12 µg/dl), with 0.5% lime pretreatment and catfish powder (1:1) (respective Fe and Hb value was 107.29 µg/dl and 11.25 µg/dl), can be used in anemia recovery.Conclusion: The best result for anemia recovery was obtained from feeding of kelor powder leaves with 0.5% lime pretreatment.